INTRASCROTAL SWELLINGS: A SINGLE CENTER CROSS-SECTIONAL PROSPECTIVE OBSERVATIONAL STUDY ON CLINICOHISTOPATHOLOGICAL PROFILE WITH REFERENCE TO DIAGNOSTIC ULTRASOUND AND PUBLIC HEALTH IMPLICATIONS. - Nabarun Manna; Debajit Das; Somnath Ghosh (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Intrascrotal swellings are a pretty common entity faced by surgeons and surgical pathologists. The etiology ranges from inflammatory, infective to neoplastic proportions. Scrotal ultrasound (USG) plays a critical role in formulating management plan as many entities respond to conservative treatment without any need of surgical intervention. Aims and Objective: The study was conducted to acquire an in-depth knowledge on varied presentations, public health implications and to evaluate the role of ultrasound imaging in the light of operative findings and histopathological examination (HPE) where definitive surgical management was carried out. Materials and Methods: The study was conducted on one hundred voluntary participants presenting with intrascrotal swelling in the surgical outpatient and emergency units at a tertiary care center following approval of the institutional ethics committee and written informed consent and assent as applicable; excluding inguinal swellings, scrotal skin lesions and moribund patients. Clinicodemographic variables, imaging results, operative record and HPE findings were assessed, analyzed and correlated with appropriate statistical principles. Results: Middle aged population between 30 and 60 years constituted the majority with a mean of 41.45 years of the study participants. Commonest intrascrotal pathology was vaginal hydrocele (62%), followed by epididymo-orchitis (40%). USG findings correlated with HPE results at a significance level of 0.05.Conclusion: The study revealed scrotal USG as an important tool to guide management and identified key areas of public health concerns to initiate awareness campaigns.